2011
DOI: 10.1111/j.1442-200x.2010.03316.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Guidelines for the Management of Respiratory Infectious Diseases in Children 2007 with focus on pneumonia

Abstract: Members of the Japanese Society of Pediatric Pulmonology and the Japanese Society for Pediatric Infectious Diseases developed the Guidelines for the Management of Respiratory Infectious Diseases in Children with the objective of facilitating the appropriate diagnosis and treatment of childhood respiratory infections. To date, a first edition (2004) and a revised edition (2007) have been issued. Many problems complicate the diagnosis of the pathogens responsible for bronchopulmonary infections in children. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
0
48
1
Order By: Relevance
“…LAMP is a nucleic acid amplification method that was developed in Japan as a simple, easy, and fast assay used to detect B. pertussis DNA (3,5). In our study, all 57 cases of microbiologically confirmed B. pertussis infections were LAMP-positive, while only 60z were culture-positive.…”
Section: Discussionmentioning
confidence: 73%
“…LAMP is a nucleic acid amplification method that was developed in Japan as a simple, easy, and fast assay used to detect B. pertussis DNA (3,5). In our study, all 57 cases of microbiologically confirmed B. pertussis infections were LAMP-positive, while only 60z were culture-positive.…”
Section: Discussionmentioning
confidence: 73%
“…After further screening, 20 guidelines meeting inclusion criteria were included for review and analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Two guidelines were excluded because newer updates were available [33,34], and two were excluded based on their language of publication [35,36]. Guideline topics included meningitis [13,14], acute otitis media [15], upper respiratory tract infections [16][17][18][19], lower respiratory tract infections [20][21][22], gastroenteritis [23], intra-abdominal infections [24], urinary tract infections [25][26][27][28], septic shock [29], and pathogen-specific infections [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…All patients underwent chest X-ray examination upon admission, and if the patient had large pulmonary lesions evident in the chest radiograph, a second chest X-ray examination was performed about 7 days after admission. A large lesion was defined when the extent of infiltration on chest radiography was more than one-third of the lung (18). The severity of pneumonia was evaluated according to the diagnostic standard for pneumonia advocated by British Thoracic Society (19).…”
Section: Methodsmentioning
confidence: 99%